Occurrence and potential risk of currently used pesticides in sediments of the Alqueva reservoir (Guadiana Basin) - Palma, Patrícia (2015)
The evaluation of sediments, concerning to pesticides, constitutes an important step for the understanding of the principal sources of contamination of the surface water. Hence, the purpose of this study was to evaluate for the first time the occurrence, distribution and risk of pesticides in sediments of the Alqueva reservoir, the largest reservoir in the Europe. For this purpose, the occurrence of 22 pesticides and some of their degradation products was determined in surficial sediments of the Alqueva reservoir. To assess the potential risk on ecosystem, the measured concentrations of pesticides were compared with regulatory and toxicological benchmarks. Of the 22 pesticides analysed, only 8 were detected. Diuron was the pesticide detected in greater concentration, followed by terbuthylazine and chlortoluron. The sediments most polluted by pesticides were from Lucefécit, constituted totally by fine particles (<0.063 mm) and with high values of organic matter, and are located nearby large agricultural fields. The risk assessment allowed us to conclude that the sediments from the Alqueva reservoir presented low risk, concerning to pesticides, for the various communities that integrate the aquatic ecosystems. However, some of the compounds detected present a high potential for bioaccumulation that may lead to their bioamplification in the trophic chain, reaching concentrations higher than their acceptable daily intake, putting, in this way the populations at risk.